The extent to which the arbitral award may be amended and appealed for nullity - علي, غسان (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The arbitration system in any dispute , whether civil , commercial or administrative, goes through three stages The first includes the agreement on arbitration , the second includes the arbitration procedures and the third stage includes a decision on the subject of the dispute with a judgment binding on the parties , Therefore some described arbitration as the beginning of an agreement the middle of which is a procedure , and the end of it is a judgment , This means that arbitration is not based on a single legal act, but rather on the basis of a single legal act, It is based on a set of interrelated legal acts , each of which differs from the other , and these acts take place in a time succession , including those related to the parties agreement to resort to arbitration , the formation of the arbitral tribunal and the arbitration ruling The arbitration award is rightly considered one of the most important stages that the arbitration system goes through beginning with the parties agreement to resolve their dispute and the implementation of the arbitral award The arbitral award is the decision issued by the arbitral tribunal and decides finally on the issues referred to it by issuing the arbitral award , the arbitral tribunal has accomplished its task that it was assigned to and therefore it is not allowed to return to the award except within the limits permitted by the law or the agreement of the parties , This principle is known as the exhaustion of the jurisdiction of the arbitral tribunal or arbitrators , and it is an established principle in the matter of the arbitrator or the arbitral tribunal and in the matter of courts whether , and if that is the general principle , Does that mean that there are no exceptions to this principle ?